Pembuatan Biofoam dari Pati Singkong dengan Tambahan Serat Selulosa dari Jerami Padi sebagai Filler - Muspira, Nazira; Fachraniah, Fachraniah; Syafruddin, Syafruddin (Politeknik Negeri Lhokseumawe, 2024)
Biodegradable foam made from starch is an alternative packaging to replace styrofoam, but foam made from starch is very fragile, sensitive to water. Additional treatment is required to increase strength, flexibility and resistance to water for commercial application. The addition of rice straw cellulose as a filler to improve the properties of the resulting biofoam. Rice straw that has been fermented using MA-11 is then washed and sieved using a 100 mesh sieve to produce cellulose. The process of making biodegradable foam uses the extrusion method. The variables used were the ratio of cassava starch and rice straw, namely 40:60, 45:55, 50:50, 55:45, 60:40 % w/w with variations in cooking time, namely 30 minutes, 40 minutes, 50 minutes, 60 minutes, 70 minutes. The results of biodegradable foam testing from cassava starch and rice straw obtained values of tensile strength, compressive strength, water absorption, and biodegradability. The tensile strength and compressive strength tests for all biofoam samples did not meet SNI standards. The results of the water absorption test that met the SNI standards were sample 45:55 minutes 30 with a value of 26.72%, and the results of the biodegradation test met the SNI standards, namely the sample 60:40 in 30 minutes with a value of 82.27% with a biodegradation time of 7 day.